The challenge of differentiating between plagiarism and intertextuality in the legal sciences - Ridha, Khene Mohamed; Djagham, Mohamed (The International tax journal, 2025)
Intertextuality is a literary phenomenon that has significantly contributed to the literary works of writers, novelists, and poets. However, it has been subject to limited study in the legal field despite its prominent importance in legal discourses, especially with the development of legal methodology and the necessity of documenting scientific research with integrity. This serves as an indication of the presence of intertextuality in legal texts, particularly in the context of citation, marginalization, comparative studies, and the mutual influence between legal schools, as well as the importation and modeling of laws within the framework of the phenomenon of legal globalization. Intertextuality has become unavoidable, whether intentional or unintentional, in international, constitutional, legislative, or regulatory legal texts. Therefore, the study will attempt to differentiate between intertextuality, which is considered a scientific practice that cannot be renounced, and academic plagiarism, which is regarded as a practice that undermines scientific integrity.